THE BASIC POINTS OF SAFE MANAGEMENT OF PREGNANCY AND DELIVERY IN PATIENTS WITH MARFAN SYNDROME - L. S. Radetskaya; A. D. Makatsariya; V. O. Bitsadze; N. M. Khamani; D. V. Mitryuk; N. A. Makatsariya (IRBIS LLC, 2017)
Marfan syndrome is dominantly inherited connective tissue diseases, associated with microfibrillar fiber connective tissue deficiency in vascular walls, heart valves, joints, dural membrane,  bones, and other organs. Diagnosis may be confirmed by clinical  criteria and molecular tests. Pregnancy bears a risk of fatal complications,  including aortic dissection, aortic root dilation, mitral valve insufficiency.  Women must be followed and managed in a high risk pregnancy unit by a team from obstetricians, cardiologists, anesthetists, pediatricians, neonatologists  and cardiac surgeons who are skilled in high risk pregnancies. This approach allows to avoid the serious maternal and fetal complications. Caesarean section should be offered for such patients, because it minimizes the hemodynamic changes, associated with vaginal delivery. Some authors recommend to perform post-cesarean hysterectomy, because of the high incidence of massive hemorrhage in postpartum.